Lease from John, Earl of Ormonde, to Francis Reynolds of a plot of ground (approximately 360 sq. feet) on the Parade in the parish of St. Patricks, Kilkenny city, for 999 years at a yearly rent of £11 7s. 6d., with a lease from John, Earl of Ormonde, to George Leech of Kilkenny city of a plot of ground of approximately 800 sq. feet) on the Parade in the parish of St. Patricks, Kilkenny city, for 999 years at a yearly rent of £11 7s. 6d., - Ormonde, John Butler, Earl of, 1740-1795 (1792)
These two plots of grounds were adjacent to each other and an archway accessible to each was made free for the use of both parties. A small map by James Healy of the plot of ground in question is attached to each of these two deeds.